Prospects of Green Leaf Manuring as an Alternative to Fertilizer Nitrogen in Agricultural Lands - Nitant, H.C. (Journal of Soil and Water Conservation, 2022)
Fertilizer nitrogen has been out of reach for farmers particularly in the dryland areas. Leucaena leaves are quite rich in nitrogen (about 3%) and decompose rapidly. Usually Leucaena is grown in different systems of agrofoffestry and as alley cropping, energy plantations or on field boundaries. The leaves are mainly used as green fodder. Further, surplus leaves of Leucaena can also be used as green manure to agricultural crops. Effect of four rates of nitrogen fertilizer (0,50,100 and 150 kg/ha) with and without green leaf manuring (Leucaena leucocephala) on nutrient uptake, fertility build-up and wheat yield was studied. Leucaena leaves (green leaves + tender twigs) incorporated in red soil (Parwa) as green leaf manuring significantly raised the yield of both grain and straw. Highest grain production was recorded when green leaf manuring enchanced the uptake to nutrients (Zn, N and P) and nitrogen use efficiency at different rates of N applied. The status of organic carbon and available nutrients (Zn, N and P) was also increased in presence of green leaf Immuring. Application of 50 kg/ha (Urea-N) alongwith Leucaena leaves resulted in higher grain production than that obtained by the application of 150 kg N/ha. This clearly indicated that for fertilizing wheat as much as 100 kg of N/ha could be substituted through Leucaena leaves (green leaf manuring). (Key words-Leucaena leaves, nutrient availability, wheat yield).